Implementing the OECD principles on water governance : indicator framework and evolving practices - Organisation for Economic Co-operation and Development (OECD studies on water, ISSN 2224-5073, 2018)
Summary.
Keywords: vesihallinto; vesiensuojelu; vesivarat; vesien käyttö; ympäristöhallinto; ympäristönsuojelu; ympäristöpolitiikka